(3GdLOjO aj GdbhGYO hGdGYQGa GdehMOI GdGYJeGOGJ GdeSJfOjI (B500s - (3YHO GdZfj(B, (3GdUZjQ MSGe GdOjfs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2003)
(3GdbhGYO GdLOjOI daMU GdeSJfOGJ h eWGHbJgG (B- (3GdeYGdLI GdJaUjdjI deSJfOGJ fbd GdHVGYI (B- (3GdGMcGe GdJj GSJMOKJgG GdbhGYO h GdGYQGa GdehMOI (B- (3GdGMcGe GdeSJMOKI deUdMI GdeSJajOs
(3HHdjhZQGajG(B: 147(3U(B. (3GdedGMb(B: 135(3U(B.s